Acceptance and utilization of teleprimary care in Sarawak - Ho, Ai Chia (Universiti Malaysia Sarawak (UNIMAS), 2013)
Teleprimary Care (TPC) is an electronic system used in healthcare to facilitate the workflow in healthcare organization and improve quality of patient care. The system which was introduced in year 2004 has been implemented in 31 health facilities throughout Sarawak, including two hospitals and six divisional health offices. To date, no proper evaluation has been done on TPC especially on the acceptance of users towards the system. The objective of this study was to analyze the characteristics of TPC users in Sarawak, their acceptances and perceptions towards the system, challenges and barriers faced and comments in improving the system. This was a cross-sectional study using quantitative research method, supplemented with qualitative data to better understand the actual feelings of system users in the field. A total of 516 TPC users throughout Sarawak were surveyed using self-administered questionnaire and 44 system users as well as system coordinators were interviewed. The overall acceptance of users towards TPC was good. Analysis revealed that job relevance, perceived usefulness, result demonstrability and subjective norms appeared to be significant influencing factors for acceptance of TPC. However, perceived ease of use, motivation and voluntariness were not strong predictors for intentions to use the system. Two-fifth of users preferred TPC system, while 28% preferred the conventional paper-based system for documentation. Users who preferred TPC system were those working in the hospital, registration officers and users who had been using the system for more than 3 years. The commonest barriers faced by users were related to technical issues, followed by database problems, disruption of face-to-face contact with patients and lack of training. Improving the server for TPC and providing training for all users were among the priorities to improve the utilization of TPC, from the users' perspectives. Clinic and Divisional coordinators played important role in TPC implementation but were limited by time constraint and financial control. In conclusion, result from the study highlighted the need for future strategies to focus on improving functionality of TPC in enhancing the workflow of users in their daily works. Supervisors and ·Divisional Health Officers need to be TPC-minded and to encourage the usage ofTPC among users in the Division. There is also an overwhelming need for tackling the technical issues of TPC and providing training for all users in order to improve the implementation of TPC.